2020
DOI: 10.1073/pnas.2003136117
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-dependent downregulation of MR1 cell surface expression

Abstract: The antigen-presenting molecule MR1 presents riboflavin-based metabolites to Mucosal-Associated Invariant T (MAIT) cells. While MR1 egress to the cell surface is ligand-dependent, the ability of small-molecule ligands to impact on MR1 cellular trafficking remains unknown. Arising from an in silico screen of the MR1 ligand-binding pocket, we identify one ligand, 3-([2,6-dioxo-1,2,3,6-tetrahydropyrimidin-4-yl]formamido)propanoic acid, DB28, as well as an analog, methyl 3-([2,6-dioxo-1,2,3,6-tetrahydropyrimidin-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 48 publications
1
74
0
Order By: Relevance
“…Most recently, using an in silico screen based on the MR1 binding pocket, Salio et al identified an intriguing effect of a novel MR1 ligand (3-[(2,6-dioxo-1,2,3,6-tetrahydropyrimidin-4-yl)formamido]propanoic acid “DB28,” which appeared to decrease, rather than increase cell surface expression of MR1, as well as competitively inhibiting activation of MAIT cells by agonist ligands ( 30 ).…”
Section: Expansion Of the Mr1 Ligand Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, using an in silico screen based on the MR1 binding pocket, Salio et al identified an intriguing effect of a novel MR1 ligand (3-[(2,6-dioxo-1,2,3,6-tetrahydropyrimidin-4-yl)formamido]propanoic acid “DB28,” which appeared to decrease, rather than increase cell surface expression of MR1, as well as competitively inhibiting activation of MAIT cells by agonist ligands ( 30 ).…”
Section: Expansion Of the Mr1 Ligand Familymentioning
confidence: 99%
“…The lower potency of the related lumazine antigens also appears to be due to their inability to form a Schiff base with the Lys 43 residue. Interestingly, the MR1 downregulating ligand, DB28, was unable to form a Schiff based with the Lys 43 residue ( 30 ). Within MAIT TCRs, there was the conservation of key residues including a highly conserved Tyr at position 95 of the CDR3 loop of the TCR α-chain.…”
Section: Understanding Mait Cell Recognition Of Mr1-presented Riboflamentioning
confidence: 99%
“…The role these ligands may play in drug-induced immune modulation through MAIT cell activation or inhibition is not yet clear. Using a similar in silico screen, Salio et al, recently expanded the library of MR1 ligands, including the first molecule that prevents MR1 egress from the ER ( 17 ). Intriguingly, this ligand binds in the MR1 A'-pocket in a non-covalent fashion and prevents MR1 surface translocation and MAIT cell activation in response to canonical ligands ( 17 ).…”
Section: Toward Defining the Mr1 Ligandomementioning
confidence: 99%
“…This model is consistent with work from McWilliam et al, who showed that re-loading of 6-FP-bound molecules was possible at 37°C but not on ice, indicating a requirement for internalization and recycling for ligand exchange to occur ( 41 ). Similarly, presentation of a set of novel MR1 ligands was reduced in cells over-expressing GPI-linked MR1 compared to those transduced with the WT protein, suggesting that a motif in the MR1 cytoplasmic tail may be required for ligand exchange and loading of some ligands ( 17 ). The notion of post-ER loading of MR1 molecules is further supported by the observation that pre-incubation with 6-FP rendered the subsequent surface expression of MR1-5-OP-RU complexes less sensitive to Brefeldin A (BFA) ( 41 ).…”
Section: Distinct and Complementary Mr1 Antigen Presentation Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation